Influência dos fatores abióticos sobre a variação espaço-temporal de paralonchurus brasiliensis (Steindachner, 1875) (pisces, sciaenidae) componente da fauna acompanhante da pesca de camarões no litoral Norte de São Paulo - Costa, Eudriano Florêncio dos Santos (2010)
Knowledge of the environmental factors influence on the spatial-temporal variation of fishes is important to fisheries management and conservation. Thus, the aim of this work was to analyze the influence of the abiotical factors on the spatial-temporal distribution of Paralonchurus brasiliensis (Pisces, Sciaenidae) caught by-catch with the shrimp fishing of Ubatuba and Caraguatatuba regions, north coast of São Paulo State. The fishes were captured every month from January to December 2002. Samples were collected by otter trawl at 5, 10, 15, 20, 25, 30 and 35m depths. The temperatures (surface and bottom), salinities (surface and bottom), sediment features and organic matters were verified for each depth. During all period of the study 12.642 specimens of P. brasiliensis were captured at Ubatuba and 17.166 at Caraguatatuba, which totalized the biomass of 267 for the first and 339kg for the other region. The females outnumbered males in fish population. The greatest values of biomass and number of individuals were registered at the summer and autumn seasons, while the lowest values were observed at the winter and spring seasons. The greatest abundances were found from 15 to 25m depth. In this study, it was verified that P. brasiliensis is a coastal waters associate species. The spatialtemporal distribution of P. brasiliensis is affected by intrusion of SACW and depth for the coastal region and by depth and sediment in sheltered areas such as Caraguatatuba